Use of tubulization (nerve conduits) in repairing nerve defects in children - Sénès, Filippo Maria (Indian J Orthop, 2015)
BACKGROUND: Direct neurorrhaphy, nerve grafting interposition and neurotization are the options for nerve repair in children, whereas few reports about using nerve conduits (tubulization) are referred to pediatrics in the literature. The authors present their experience about nerve repairing by means of nerve tubes during the developmental age when the harvesting of nerve grafts and also vein grafts of adequate caliber for bridging nerve defects is difficult. A critical review of their case series offers indications for using nerve conduits in pediatrics. MATERIALS AND METHODS: Fifteen patients were treated using the nerve tubulization; nine patients were affected by obstetrical brachial plexus palsy (OBPP) while six were suffering from peripheral nerve injuries (PNIs). RESULTS: In patients suffering from OBPP, we observed 1 good, 3 fair and 5 bad results. In the PNI group, we observed 4 patients who had good results while only 2 had a bad outcome. No fair results were observed. CONCLUSIONS: In peripheral nerve repairing in children by using nerve conduits, the outcome has been widely effective even when dealing with mixed and motor nerve, thus nerve tubulization might be considered as an alternative to nerve grafting. Conversely, considering the uncertain result obtained in brachial plexus repairing, the conduits cannot be considered as a first choice of treatment in brachial plexus reconstruction.